ANALISIS RASIO KINERJA KEUANGAN PROFITABILITAS PT WIJAYA KARYA (PERSERO) TBK. PERIODE 2014 - 2018 - Irwin Ananta Vidada; Ratiyah Ratiyah; Denny Erica; Hartanti Hartanti (Universitas Pendidikan Ganesha, 2019)
In estimating the risk in the face of uncertainty , companies can use analysis as a financial report estimated future formulation of the plans . Use report analysis a finance company capable of know estimation the work of these efforts division in his company. To know the financial performance of corporations in this is done through the profitability analysis ( rentabilitas ). Through the ratio of the company capable of measuring the extent to which the company ability to obtain profit. Objectives in this research is to investigate and to identify the financial performance of pt wijaya karya ( persero ) tbk a period of 2014 until 2018. In this research data collection used through via a observation and the literature study with reference to the company financial performance data. Research methodology in the writing of this is done through which is done based on the ratio of the with of a quantitative approach . Observation data to the financial pt wijaya karya ( persero ) tbk the period 2014 until 2018 . Based on the results of the analysis can summarized in general during the past year observation data ratio in the ratio of the gpm, npm, oim roe and had fluctuations caused earnings up and down and ratio in roa was decreasing.keywords : Ratio Analysis, Financial Performance, Profitabiliy